Nonlinear thermal analysis of timber cross-sections via CS-ASA/FA and GiD coupling - Jackson Silva da Rocha Segundo; Caroline Aparecida Ferreira; Ricardo Azoubel da Mota Silveira; Rafael Cesário Barros; Dalilah Pires; Ígor José Mendes Lemes (REM: International Engineering Journal)
Abstract In fires, situations in which high temperatures are evident, it is noticed that the materials have their physical and resistance properties deteriorated. In the structural systems considered under these fire conditions, there is a considerable loss of load capacity and strength. Therefore, the temperature progression evaluation in the structural elements’ cross-sections is essential for understanding their behavior under high temperature. Thermal analysis allows determining the complete temperature field in the element cross-section from boundary conditions provided by some adopted fire model, taking into account the variation in the material thermal properties with the temperature increase. Timber, being a combustible material, requires knowledge and adequate modeling of its behavior and performance when kept in a fire situation. This anisotropic material, with fibers containing irregular flammable knots, has been widely used in civil construction. Thus, this research aims to carry out numerical thermal analysis through the Computational System for Advanced Structural Analysis/Fire Analysis (CS-ASA/FA), with the preand post-processing graphical tools provided by the GiD platform, of timber structural elements’ cross-sections used in civil construction. The results obtained are compared with those of literature, demonstrating the ability of this CS-ASA/FA module and GiD coupling to provide the necessary information for the evaluation of timber cross-sections in a fire situation.